Incidental Detection of Medullary Thyroid Carcinoma by 68Ga-DOTATATE PET/CT in a Patient With Neuroendocrine Tumor Liver Metastases. (February 2018) - Mahajan, Sonia; Shaha, Ashok; Grewal, Ravinder K.
Abstract : Abstract: 68 Ga-DOTATATE, a positron-emitting somatostatin analog, has been approved by the Food and Drug Administration for imaging neuroendocrine tumors (NETs). The presence of a second primary malignancy is common in NETs; however, synchronous primary malignancy in the thyroid has rarely been reported. The value of 68 Ga-DOTATATE in medullary thyroid cancer is being investigated and is currently recommended for use when treatment with somatostatin analogs is an option. We present a 55-year-old man with abdominal pain associated with well-differentiated NET liver metastases and incidental medullary thyroid carcinoma demonstrated on a 68 Ga-DOTATATE PET/CT.